Clinical research in dementia: A perspective on implementing innovation. Issue 11 (24th March 2022) - Boccardi, Marina; Handels, Ron; Gold, Michael; Grazia, Alice; Lutz, Michael W.; Martin, Mike; Nosheny, Rachel; Robillard, Julie M.; Weidner, Wendy; Alexandersson, Jan; Thyrian, Jochen René; Winblad, Bengt; et al.
Abstract: The increasing global prevalence of dementia demands concrete actions that are aimed strategically at optimizing processes that drive clinical innovation. The first step in this direction requires outlining hurdles in the transition from research to practice. The different parties needed to support translational processes have communication mismatches; methodological gaps hamper evidence‐based decision‐making; and data are insufficient to provide reliable estimates of long‐term health benefits and costs in decisional models. Pilot projects are tackling some of these gaps, but appropriate methods often still need to be devised or adapted to the dementia field. A consistent implementation perspective along the whole translational continuum, explicitly defined and shared among the relevant stakeholders, should overcome the "research‐versus‐adoption" dichotomy, and tackle the implementation cliff early on. Concrete next steps may consist of providing tools that support the effective participation of heterogeneous stakeholders and agreeing on a definition of clinical significance that facilitates the selection of proper outcome measures.